Low-frequency transcranial magnetic stimulation for enhancing communication in children with Autism and Specific Language Impairment (International Journal of Biology and Chemistry, 2026)
To evaluate whether low-frequency transcranial magnetic stimulation (TMS) is associated with improvement in speech-language function in children with autism spectrum disorder (ASD) and Specific Language Impairment (SLI), a treatment response difference by stimulation frequency and cortical target was assessed. This retrospective observational study analyzed clinical data from 131 children treated at Neurolab Neurorehabilitation Center (Almaty, Kazakhstan), between April 3, 2023, and July 30, 2024. The cohort included 58 children with ASD and 73 children with SLI. Speech-language function was rated before and after treatment using a structured 10-point clinical scale. TMS was delivered to the bilateral dorsolateral prefrontal cortex (DLPFC), with additional stimulation of Broca's and/or Wernicke's areas in selected participants. Frequencies of 0.3 Hz, 0.5 Hz, and 1.0 Hz were analyzed. Each course consisted of 10 daily sessions. Across the total cohort, mean speech-language rating improved from 3.46 to 3.96 points, with a mean improvement of 0.50 points. Improvement was greater in children with ASD than in children with SLI (0.83 vs. 0.25 points). The strongest response was observed in the ASD subgroup treated at 1.0 Hz, where mean improvement reached 2.13 points. In an adjusted linear regression model, the ASD x 1.0 Hz interaction remained significant (coefficient=1.55, p=0.004), while number of treatment courses was positively associated with improvement and motor delays were negatively associated with improvement. Low-frequency TMS was associated with improvement in clinician-rated speech-language function, but the effect was not uniform across stimulation protocols. The findings support the potential of TMS as a protocol-sensitive neuromodulation approach and indicate the need for prospective studies comparing stimulation parameters directly. Key words: transcranial magnetic stimulation, autism spectrum disorder, specific language impairment, low-frequency stimulation, speech development, neuromodulation.